The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/nu13030804
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Affects Metabolic and Transcriptomic Profiles and Attenuates Features of Metabolic Syndrome in Adult Male Rats

Abstract: Ellagic acid, a natural substance found in various fruits and nuts, was previously shown to exhibit beneficial effects towards metabolic syndrome. In this study, using a genetic rat model of metabolic syndrome, we aimed to further specify metabolic and transcriptomic responses to ellagic acid treatment. Adult male rats of the SHR-Zbtb16Lx/k.o. strain were fed a high-fat diet accompanied by daily intragastric gavage of ellagic acid (50 mg/kg body weight; high-fat diet–ellagic acid (HFD-EA) rats) or vehicle only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Moreover, rutin could be a neuroprotective agent, which improved the glutamate metabolism of brains in rats and prevented glutamate excitotoxicity [ 33 ]. In addition, ellagic acid could ameliorate features of metabolic syndrome [ 34 ]. Furthermore, ellagic acid could decrease the risk of diabetes mellitus by reducing oxidative stress, alleviating inflammation and improving insulin resistance [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, rutin could be a neuroprotective agent, which improved the glutamate metabolism of brains in rats and prevented glutamate excitotoxicity [ 33 ]. In addition, ellagic acid could ameliorate features of metabolic syndrome [ 34 ]. Furthermore, ellagic acid could decrease the risk of diabetes mellitus by reducing oxidative stress, alleviating inflammation and improving insulin resistance [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A HRCHFC diet administered to animals causes oxidative stress which is either enzymatically or non-enzymatically reflected as higher level of TBARS or reduced levels of SOD, CAT, GPx, GSTs, and GSH ( Aziz et al, 2013 ). Earlier studies reported that increased oxidative stress in HRCHFC-fed rats is usually an outcome of inflammation, insulin resistance, hypertension, dysregulated adipocytokines, and NASH ( Kabelova et al, 2021 ). Oxidative stress develops with increased ROS and reduced antioxidant enzymes, resulting in excessive molecular oxygen and hydrogen peroxide that lead to initiate lipid peroxidation ( Sharma et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…When metabolized by the intestinal microbiota, this phytochemical forms urolithins A, B, C, or D, whose study is interesting as modulators of OS and its anti-inflammatory properties, mostly [ 164 ]. The sources are nuts and some seeds in food, but it is mainly found in fruits at high concentrations, including blackberries, raspberries, cherries, and the red pomegranate [ 165 , 166 ]. In recent years, ellagic acid’s role in MetS, diabetes, obesity, and cardiovascular conditions, including hypertension, atherosclerosis, and endothelial dysfunction, has been investigated, alongside its properties in reducing OS, enhancing lipid profile and cholesterol metabolism, decreasing inflammatory processes, and improving insulin secretion and glucose uptake [ 167 , 168 ].…”
Section: Hivmentioning
confidence: 99%